2002
DOI: 10.1002/arch.10052
|View full text |Cite
|
Sign up to set email alerts
|

Age‐dependent response to insecticides and enzymatic variation in susceptible and resistant codling moth larvae

Abstract: Insecticide resistance in the codling moth, Cydia pomonella, partly results from increased metabolic detoxification. The aim of this study was to follow the age variations in larval susceptibility to deltamethrin and teflubenzuron in one susceptible (S) strain, and two resistant (Rv and Rt) ones selected for resistance to deltamethrin and diflubenzuron, respectively. The age variation of the activities of cytochrome P450-dependent monooxygenase (MFO), glutathione S-transferases (GST), and esterases in S and bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
72
0
3

Year Published

2004
2004
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(80 citation statements)
references
References 48 publications
3
72
0
3
Order By: Relevance
“…Neonate progeny were selected by exposure to increasing concentrations of diflubenzuron (for the Rdfb strain) or deltamethrin (for the RΔ strain) that induced 50% mortality for the first ten generations at concentration high enough to kill all susceptible larvae for 20 following generations. At the end of this selection regime, individuals of Rdfb and RΔ strains expressed homogeneously enhanced mixed-function oxidase (mfo) and glutathione S-transferase (GST) activities (Sauphanor et al 1997;Bouvier et al 2002). In addition, individuals from the RΔ strain were homozygous for a resistance allele (kdr-type) at the sodium channel gene Brun-Barale et al 2005).…”
Section: Laboratory Strainsmentioning
confidence: 99%
“…Neonate progeny were selected by exposure to increasing concentrations of diflubenzuron (for the Rdfb strain) or deltamethrin (for the RΔ strain) that induced 50% mortality for the first ten generations at concentration high enough to kill all susceptible larvae for 20 following generations. At the end of this selection regime, individuals of Rdfb and RΔ strains expressed homogeneously enhanced mixed-function oxidase (mfo) and glutathione S-transferase (GST) activities (Sauphanor et al 1997;Bouvier et al 2002). In addition, individuals from the RΔ strain were homozygous for a resistance allele (kdr-type) at the sodium channel gene Brun-Barale et al 2005).…”
Section: Laboratory Strainsmentioning
confidence: 99%
“…Enhanced levels of activity of certain metabolic detoxifying enzyme systems such as esterases, mixed function oxidases (MFO), and glutathione S-transferase (GST) have been suggested for conferring resistance. A low activity of general esterases in adult moths resistant to parathion (Bush et al, 1993) and differences in GST and MFO activities in insects resistant to deltamethrin October 2004 and diflubenzuron (Bouvier et al, , 2002Sauphanor et al, 1997) have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…The codling moth, Cydia pomonella (L.), and other insects in temperate areas enter diapause in response to short days (Steinberg et al 1992), and therefore some active life stages may not be found in the orchards during determined periods of the year. For codling moth the highest levels of deltamethrin resistance were recorded in late instars of resistant strains (Rv and Rt) of this insect, although Rv neonates exhibited enhanced resistance to deltamethrin (Bouvier et al 2002).…”
Section: Discussionmentioning
confidence: 93%